Modelagem matemática e controle de atitude e posição do quadrotor - Benigno, Tayara Crystina Pereira (2015)
With advances in technology and the popularization of the use of Unmanned Aerial Vehicles (UAV's) so does the need to use more robust and more effective control techniques. Among the various types of unmanned aerial vehicles, this paper will focus on quadrotor model, which has a mechanical structure in the form of x, whose ends have an engine and propeller assembly, where the rotation of this group is responsible for the lift and the movements developed by quadrotor. This feeling, aiming to apply drivers that provide stability to the dynamic system. This study aims to conduct mathematical modeling using the Euler-Lagrange. With this, it is proposed a PID controller (Proportional Integral Derivative) to maintain stable the three orientation angles and height to a desired value. The development of the proposed controller will be validated via simulation confirming the application feasibility of the technique presented stability